Introduction to cytogenetics 1 - SenGupta, Sioban (Henry Stewart Talks, 2010)
Definitions, Cytogenetics, Chromosomes, Karyotyping, G banding, Normal male karyogram, Q banding, R banding, C banding, ISCN, Types of chromosome abnormalities, Aneuploidy, Sex chromosome abnormalities, Down syndrome, trisomy 21, Edwards syndrome, trisomy 18, Patau syndrome, trisomy 13, Robertsonian translocations, Reciprocal translocations, Inversions, Insertions, Deletions, Ring chromosome, Isochromosomes, ESAC